2007
DOI: 10.4038/jnsfsr.v35i2.3674
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of metabolic and insensitive acetylcholinesterase mechanisms in insecticide resistance of rice insect pests and predatory populations from Batalagoda, Sri Lanka

Abstract: Biochemical assays were carried out within one week of storage to determine the activity levels of major enzyme groups (i.e carboxylesterases, glutathione S-transferases and monooxygenases), which are involved in insecticide metabolism. Native polyacrylamide gels were run with crude homogenates to resolve carboxylesterase isozymes. Sensitivity of the organophosphate and carbamate target site acetylcholineesterase was tested by inhibiting the enzyme with propoxur.N. lugens, S. furcifera and N. virescens showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Preservation of high resistance to DDT has been detected not only in malaria vectors but also in other Sri Lankan insect pest populations, such as the populations of dengue vectors Aedes aegypti and Ae. albopictus [45], Japanese encephalitis vectors Culex tritaeniorhynchus and Cx gelidus [46], bed bug Cimex hemipterus [47], sand fly Phlebotomus argentipes [48], cattle tick Rhipicephalus microplus [49] and a range of agricultural insect pests [50]. It has been suggested that underlying mechanisms, especially the enhanced GST-mediated metabolism, initially selected by exposure to DDT, have been subsequently selected by exposure to organophosphates and pyrethroids [42,51,52].…”
Section: Development Of Insecticide Resistancementioning
confidence: 99%
“…Preservation of high resistance to DDT has been detected not only in malaria vectors but also in other Sri Lankan insect pest populations, such as the populations of dengue vectors Aedes aegypti and Ae. albopictus [45], Japanese encephalitis vectors Culex tritaeniorhynchus and Cx gelidus [46], bed bug Cimex hemipterus [47], sand fly Phlebotomus argentipes [48], cattle tick Rhipicephalus microplus [49] and a range of agricultural insect pests [50]. It has been suggested that underlying mechanisms, especially the enhanced GST-mediated metabolism, initially selected by exposure to DDT, have been subsequently selected by exposure to organophosphates and pyrethroids [42,51,52].…”
Section: Development Of Insecticide Resistancementioning
confidence: 99%
“…The common mechanisms of metabolic resistance to insecticides include enhanced carboxyl-esterase (CarE), glutathione S -transferases (GST), and cytochrome P450 monooxygenase (MFO) activity [ 13 , 14 , 15 ]. The insensitivity of the target site to organophosphates and pyrethroids is related to the activity of acetylcholinesterase (AChE) [ 16 ]. The correlations between detoxifying enzymes and insecticide resistance have been reported extensively [ 4 ], including the overexpression of enzymatic detoxification involved in resistance in P. xylostella [ 9 ].…”
Section: Introductionmentioning
confidence: 99%